Studi Kelayakan Pengembangan Bandar Udara Depati Parbo Kerinci - Kurniyadi, Amri; Mulyani, Rini; Khadavi, Khadavi; Carlo, Nasfryzal; Utama, Lusi (Universitas Batanghari Jambi, 2024)
To support the current tourism sector, Kerinci Regency has an airport called Depati Parbo. The development of this airport really needs to be implemented, considering that this airport is the only airport in Jambi province that has the potential to be developed and improved. The problem in this research is what parameters need to be reviewed to assess the feasibility of developing Depati Parbo Airport, and what are the evaluation results and recommendations for the feasibility of developing Depati Parbo Airport. The aim of this research is to identify the parameters of the technical and financial aspects of the feasibility of developing Depati Parbo Airport, carry out a feasibility evaluation and provide recommendations for the feasibility of developing Depati Parbo Airport. This research method is a combination of qualitative and quantitative, that is, both support each other, in order to obtain maximum results. From the results of the analysis, it was found that the NPV (Net Present Value) was 12,441,161,179.80, BCR (Benefit Cost Ratio) 9.70%, IRR (Internal Rate of Return) 41%, although this is sufficient, there is still a need to optimize the dealer's income Depati Parbo Airport, so there is no need to increase the capacity of Depati Parbo Airport, but it is necessary to optimize Depati Parbo airport revenue.